A Study of the Role of Salt on the Southern Silk Road from Chinese Historical Documents: A Case Study of the Salt Industry in Sichuan and Yunnan Provinces - Sriratanaban, Suphacha; Gu, Mengyu (Thai Journal of East Asian Studies, 2025)
This article examines the role of salt on the Southern Silk Road by analyzing the development of the salt industry in Sichuan and Yunnan provinces, using ancient Chinese documents as primary sources. Results are that sodium chloride has two key significant aspects: First, salt functioned as a strategic resource in the economic structure of the imperial Chinese state. Sichuan and Yunnan were major centers of salt production starting from the Qin and Han dynasties. Continuous technological advances expanded the salt industry, making the two provinces into key distribution centers. The imperial state strictly monopolized and taxed salt, establishing specialized administrative agencies to oversee its production, trade, and taxation. The market was regulated by issuing salt trade licenses. The state monopoly on salt generated vital royal court revenue and controlled local economies, supported military logistics, and reinforced political stability. Therefore, salt was a strategic resource linked to the public livelihood, economic structure, and state security. Secondly, salt was an essential commodity and currency in local economies, particularly in frontier areas. In Yunnan province borderlands, part of the Southern Silk Road network connecting to Myanmar, Thailand, and Laos, salt was a basic daily product and in certain areas, used as a trade value unit. This was especially so in ethnic group exchanges and at community markets, reflecting the flexibility of regional economies where formal currency systems were inchoate.